Variability in Thule Inuit Subsistence Economy: A Faunal Analysis of OkRn-1, Banks Island, N.W.T. - Kotar, Kathryn (Scholarship@Western, 2016)
This thesis presents a zooarchaeological analysis of animal remains recovered from a late Thule qarmaq at the OkRn-1 archaeological site (ca. 1450 – 1650 AD) on Banks Island, NWT. The main objectives were to: 1) document animal exploitation in the qarmaq; 2) determine the season of occupation of the qarmaq; 3) assess change in Thule subsistence strategies on Banks Island over time; 4) identify similarities/differences between OkRn-1 and contemporary sites in the western Canadian Arctic. Ringed seal was the dietary staple of the qarmaq and Arctic fox were exploited for their pelts. The presence of migratory species and the demographic profile of ringed seals suggest that the qarmaq was occupied in the late winter, spring, and fall. Comparisons between early and late Thule assemblages on Banks Island, and between OkRn-1 and contemporary sites, reveal variability in subsistence driven by local landscape/climate, season of occupation, variability in settlement organization, and social change.